DEMOKRASI MEMBANGUN KEKUASAAN - Parlindungan S, Gokma Toni (Ensiklopedia of Journal, 2024)
Academic democracy has no single meaning. Because of this theoretical problem, when it is applied in state administration, things happen that are not the same between one country and another. However, in fact, in this understanding of democracy there are values that are universal. These values can be used as a minimum measure of whether a country consistently implements the principles of democracy or not. This means that these values are a condition for whether a country adheres to a democratic system or not.Keywords: Democracy, Power.